Effect of deposition temperature on structure and properties of Nd2O3 thin films prepared by magnetron sputtering. (November 2019) - Shao, Mingyang; Huang, Yabo; Liu, Jinlong; Jia, Xin; An, Kan; Chen, Liangxian; Wei, Junjun; Li, Chengming
Abstract: Nd2 O3 film is a functional film with great potential application value. In this paper, thinNd2 O3 film was prepared on the surface of Si substrates using RF magnetron reactive sputtering. Nd2 O3 film with different crystal structures were controlled by changing the deposition temperature. The results show that the Nd2 O3 film with a cubic structure can be obtained at 150 °C, while a hexagonal structure appears at 250 °C and above. The refractive indices of the cubic and hexagonal Nd2 O3 films were 1.736 and 2.130, respectively. Moreover, the principle of the influence of deposition temperature on the refractive index of the film was illustrated. The hardness and the elastic modulus of the cubic Nd2 O3 film were 6.3 GPa and 102 GPa, respectively, which are much lower than the 9.9 GPa and 145 GPa of the hexagonal Nd2 O3 film. In addition, with a double-sided cubic Nd2 O3 film, the maximum transmittance of the diamond film reached 87.54%. The results show that the Nd2 O3 film is an anti-reflection film suitable for optical applications. Highlights: Nd2 O3 films with cubic and hexagonal structures were prepared, respectively. The mechanical and optical properties of two kinds of Nd2 O3 films were compared. Hexagonal Nd2 O3 film shows hardness of 9.9 GPa and elastic modulus of 145 GPa. Diamond presents the maximum transmittance of 87.54% at 11.2 μm with Nd2 O3 films.